Respuestas

2013-01-12T23:16:58+01:00

Primer Forma: 

 

22x+17y = 49 (1/17) = 22/17x+y = 49/17

 

31x-26y = 119 (1/26) = 31/26x-y = 119/26

 

 

22/17x+y = 49/17

31/26x-y = 119/26

______________

 

1099/442x = 3297/442

 

x = 329/442.442/1099

x = 3

 

 

*Reemplazamos para hallar el valor de Y

 

22x+17y = 49   22.3+17y = 49 66+17y = 49 17y = 49-66 17y = -17 y = -17/17 y = -1   Segunda Forma:   22x+17y = 49 (1/22) = x+17/22y = 49/22 31x-26y = 119 (-1/31) = -x+26/31y = -119/31     x+17/22y = 49/22 -x+26/31y = -119/31  _______________   1099/682y = -1099/682    y = -1099/682.682/1099 Y = -1   * Para Hallar X   22x+17y = 49 22x+17.(-1) = 49 22x = 49+17 22x = 66  x = 3